Analisis Relasi Makna dalam Editorial Media Indonesia - Rewina Fitra Dianti; Desi Sukenti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Semantics is a branch of linguistics that studies meaning. One of the studies of semantics is the relation of meaning which is interpreted as a link between one form of language and another. In the September 2022 editorial of Media Indonesia, there are words and sentences that are related to meaning. This study aims to describe, analyze, interpret, and conclude the relation of meaning in Media Indonesia editorial. The approach used is a qualitative approach. The type of research used is literature study. The method used in this research is content analysis method. Data collection techniques used are hermeneutic techniques and documentation techniques. The validity technique used is theoretical triangulation. Based on the results of data analysis, 7 forms of meaning relations were obtained in the September 2022 editorial of Media Indonesia, namely: 1) synonyms; 2) antonyms; 3) polysemy; 4) homonymy; 5) hyponymy; 6) ambiguity; and 7) redundancy. Thus, the results of this study indicate that Media Indonesia has words and sentences that are related to meaning which makes these sentences firm and interesting. However, not everyone masters such a broad vocabulary. Therefore, the editor must pay attention to words and sentences before being published to the public.